Microwave effects on soluble substrate and thermophilic digestibility of activated sludge - Coelho, Nuno Miguel Gabriel; Droste, Ronald L; Kennedy, Kevin J (Water environment research, 2014)
Thickened waste-activated sludge (TWAS) was subjected to microwave pretreatment and athermal irradiation. The soluble phase of each type of TWAS pretreatment was subject to ultrafiltration in series using progressively smaller pore-size membranes (300, 100, 10, and 1 kDa) and biodegradability tests. Microwave pretreatment solubilizes a considerable amount of the suspended organic substrate, but athermal irradiation also causes solubilization of organic matter, although at a smaller scale than microwave. Proteins are particularly sensitive to athermal irradiation, and both microwave and athermal irradiation are capable of changing the size distribution of dissolved organic matter. Athermal irradiation and microwave have a substantially different effect on thermophilic anaerobic biodegradability of the various size fractions obtained after ultrafiltration. Slight inhibition and decrease in total biogas production was measured in some microwave tests. Athermal irradiation does not cause a decrease in maximum biogas production rate in any test and increases slightly biogas production.